Influence law of multipoint vibration load on slope stability in Xiaolongtan open pit mine in Yunnan, China - Liu, Han; Ji-sen, S.; Hanif, Noor Rosly; Wen-jia, X.; Xin, L.; Hong-wen, J.; Li, M. (Central South University, 2015)
The purpose of this work was to explore the influence law of vibration load on rock mass structure and slope stability. Based on the type and transmission way of vibration stress wave, the main stress in the horizontal and vertical directions was analyzed and the superposition effect of the stress wave was revealed. After the mechanical analysis of the sliding mass, the calculation formulas of the anti-sliding force and the sliding force were derived and the damage mechanism of blasting vibration to the structural plane was defined. In addition, according to the structure and lithologic parameter of the slope as well as the vibration monitoring data, the west slope stability of Xiaolongtan open pit mine was analyzed. The results show that the time-dependent stability factor is proportional to the vibration speed and the peak values appear at the same time. Vibration load promotes the breakage of the structural plane leading to the drop of the west slope stability factor by 0.23%. Under the multipoint simultaneous blasting, the fluctuating laws of the stability factors are consistent. The more the start-up points are, the higher the weakening degree to the slope stability is. Under the multipoint allochronic blasting, the stability factor depends on the synthetic waveform structure of all vibration waves. The greater the blasting time difference is, the lower the weakening degree to the slope stability is. Selecting the reasonable quantity of start-up points and time difference could fully reduce the adverse influence of vibration load to slope stability.